CHROMATOGRAPHIC ANALYSIS OF CAROTENOIDS AND ANTHOCYANINS IN SWEET CHERRY AUTUMN LEAVES USED IN ORNAMENTAL LANDSCAPES - LISANDRU, Tabita-Teodora; BUNEA, Andrea; FÜSTÖS, Adrian; DUMITRAȘ, Adelina Florica; BUNEA, Claudiu-Ioan; DAN, Valentin Sebastian; GÁL, Emese; MITRE, Viorel (Studia Universitatis Babeș-Bolyai Chemia, 2018)
The pigments composition of sweet cherry leaves (Prunus avium L.) were identified for the first time under the climate conditions of Cluj-Napoca. Five cherry tree varieties (Merchant, Early Red, Lapins, Burlat, Kordia) have been selected in autumn of 2016 in order to identify and quantify the major pigments in these types of leaves. Five carotenoids (lutein, β-carotene, zeaxanthin, cis-β-caroten, α-carotene) and one major anthocyanin (cyanidin-3-glucoside) were found in cherry leaves. The main carotenoids identified in all cultivars were lutein (340.55 µg/g), followed by β-carotene (147.06 µg/g). Early Red cultivar had the highest content of cyanidin-3-glucoside (17.96 mg/100g), followed by Kordia variety (11.46 mg/100g). Cyanidin-3-glucoside is responsible for red coloration of the leaves, meanwhile lutein, β-carotene, zeaxanthin, cis-β-carotene and α-carotene are providing yellow to orange colours of the leaves. The coloration of sweet cherry leaves, given by the accumulation of anthocyanin and carotenoids in autumn, makes this species suitable for ornamental use in urban design.